Maternal stress, child behavior and the promotive role of older siblings - Federica Amici; Stefan Röder; Wieland Kiess; Michael Borte; Ana C. Zenclussen; Anja Widdig; Gunda Herberth (BMC, 2022)
Abstract Background In the first years of their lives, children develop the cognitive, social and emotional skills that will provide the foundations for their lifelong health and achievements. To increase their life prospects and reduce the long-term effects of early aversive conditions, it is therefore crucial to understand the risk factors that negatively affect child development and the factors that are instead beneficial. In this study, we tested (i) the effects of different social and environmental stressors on maternal stress levels, (ii) the dynamic relationship between maternal stress and child behavior problems during development, and (iii) the potential promotive (i.e. main) or protective (i.e. buffering) effect of siblings on child behavior problems during development. Methods We used longitudinal data from 373 mother-child pairs (188 daughters, 185 sons) from pregnancy until 10 years of age. We assessed maternal stress and child behavior problems (internalizing and externalizing) with validated questionnaires, and then used linear mixed models, generalized linear mixed models and longitudinal cross-lagged models to analyze the data. Results Our results showed that higher maternal stress levels were predicted by socio-environmental stressors (i.e. the lack of sufficient social areas in the neighborhood). Moreover, prenatal maternal stress reliably predicted the occurrence of behavior problems during childhood. Finally, the presence of older siblings had a promotive function, by reducing the likelihood that children developed externalizing problems. Conclusions Overall, our results confirm the negative effects that maternal stress during pregnancy may have on the offspring, and suggest an important main effect of older siblings in promoting a positive child development.